2018
DOI: 10.1186/s12859-018-2161-y
|View full text |Cite|
|
Sign up to set email alerts
|

The cytidine deaminase under-representation reporter (CDUR) as a tool to study evolution of sequences under deaminase mutational pressure

Abstract: BackgroundActivation induced deaminase (AID) and apolipoprotein B mRNA editing enzyme, catalytic polypeptide-like 3 (APOBEC3) are deaminases that mutate C to U on single-stranded DNA (ssDNA). AID is expressed primarily in germinal center B-cells, where it facilitates affinity maturation and class-switch recombination. APOBEC3 are a family of anti-viral proteins that act as part of the intrinsic immune response. In both cases, there are particular sequence motifs, also known as “mutation motifs”, to which these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 34 publications
(29 reference statements)
0
21
0
Order By: Relevance
“…The quantification of AID and A3 hotspot representation in the gamma-herpesviruses was determined using the cytidine deaminase representation reporter (CDUR) (Shapiro, Meier, and MacCarthy 2018). This reporter consists of different shuffling algorithms that generate a null distribution of 1,000 random sequences from a subject sequence, and compares the number of hotspots in the sequence of interest to this null model.…”
Section: Methodsmentioning
confidence: 99%
“…The quantification of AID and A3 hotspot representation in the gamma-herpesviruses was determined using the cytidine deaminase representation reporter (CDUR) (Shapiro, Meier, and MacCarthy 2018). This reporter consists of different shuffling algorithms that generate a null distribution of 1,000 random sequences from a subject sequence, and compares the number of hotspots in the sequence of interest to this null model.…”
Section: Methodsmentioning
confidence: 99%
“…Different bioinformatics approaches have been used to search for evidence of an A3 evolutionary footprint in viral genomes [17,[29][30][31][32][33]35,36]. In this study, we adapted and extended the Warren et al approach [29] to carry out a general screening for the A3 footprint of the genomes of all currently annotated human viruses.…”
Section: Plos Pathogensmentioning
confidence: 99%
“…The A3 footprint is defined as the under-representation of A3-targeted motifs. Different approaches have been devised to estimate the over/under-representation of a given motif [17,[29][30][31][32][33]35,36].…”
Section: Definition Of the A3 Footprintmentioning
confidence: 99%
See 1 more Smart Citation
“…Following publication of the original article [ 1 ], the authors reported that Figs. 1 and 3 were interchanged.…”
Section: Correctionmentioning
confidence: 99%